2015
DOI: 10.3109/00016357.2015.1023353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carisolv system vs traditional rotating instruments for caries removal in the primary dentition: A systematic review and meta-analysis

Abstract: This systematic review indicates that the clinical efficacy of chemo-mechanical removal with Carisolv seems as reliable as the rotary instruments. However, the results should be interpreted cautiously due to the heterogeneity among study designs and to the shortage of available data. Further large-scale, well-designed randomized controlled trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
2
20
1
3
Order By: Relevance
“…For research topics, caries was the hottest topic at 2010‐2016 IADR annual meetings, and researches about dental trauma had the highest publication rate . Although regression analysis has demonstrated that topics were irrelevant with publication, the topics that have been frequently presented and published may reflect the focus of paediatric dental research in the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For research topics, caries was the hottest topic at 2010‐2016 IADR annual meetings, and researches about dental trauma had the highest publication rate . Although regression analysis has demonstrated that topics were irrelevant with publication, the topics that have been frequently presented and published may reflect the focus of paediatric dental research in the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…For research topics, caries was the hottest topic at 2010-2016 IADR annual meetings, and researches about dental trauma had the highest publication rate. 19 Although regression analysis has demonstrated that topics were irrelevant with publication, the topics that have been frequently presented and published may reflect the focus of paediatric dental research in the past 10 years. Dental caries has been the most popular oral disease of children, and its treatment and prevention still challenged us, 20 whereas dental trauma, the second most popular oral disease of children, can cause many irreversible problems, such as loss of teeth and impairment of facial aesthetics.…”
Section: F I G U R E 3 Publication Rate By Conference Yearmentioning
confidence: 99%
“…Az abszolút izolálás használata mellett szükséges az exhaustor folyamatos használata is, a hagyományos nyálszívóval párhuzamosan [34]. Olyan esetekben, amelyekben nem kivitelezhető a kofferdam használata, megfontolandó az aeroszolképződéssel nem járó megoldások alkalmazása, mint például a kémiai caries eliminatio [35,36] (például Carisolv, D-Solv) vagy az ART-(Atraumatic Restorative ÖSSZEFOGLALÓ KÖZLEMÉNY Treatment) technika [37]. Ajánlott, hogy a kezelések végzése minden esetben négykezes technikával történjen, vagyis alapvetően két fogászati asszisztens együttes jelenléte szükséges a kezelések elvégzéséhez [8,38].…”
Section: A Fogászati Beavatkozásokkal Kapcsolatos Sajátosságokunclassified
“…Nie odnotowano istotnej statystycznie różnicy w skuteczności usuwania zębiny próchnicowej pomiędzy ocenianymi metodami. Jednoznacznie wykazano, że zastosowanie preparatu Carisolv wymaga dużo więcej czasu, ale jednocześnie dużo rzadziej potrzebne jest podanie znieczulenia [11].…”
Section: Wiertłaunclassified